Mengelola Stres dengan Inemuri: Studi Fenomenologi pada Karyawan PT TMI - Bahrain, Faizal; Leofianti, Annisa Rizkiayu (Inquiry: Jurnal Ilmiah Psikologi, 2024)
Abstract PT TMI is a company providing professional training services that focuses on human resource development and occupational health and safety (K3). PT TMI’s coverage location covers all regions in Indonesia, especially in big cities. Therefore, PT TMI employees are required to always be ready for the dynamics of client companies, and have a spirit of innovation to be able to provide the best service. In order to ensure performance and support the creation of a climate of innovation within PT TMI, management implemented a new program called Inemuri, which was inspired by Japanese culture. They believe that through the implementation of it’s, employee work stress can be maintained, so that they are better able to produce the best performance. This research aims to explore the role of the Inemuri program on the stress levels of PT TMI employees using a qualitative phenomenological model method. Researchers tried to explore the role of the Inemuri Program on employee stress levels through interview methods with 3 (three) employees, each from a different division. The research results show that the Inemuri program has a role in reducing employee stress levels, which is characterized by feelings of happiness, a fresher body, refocused cognitive abilities and enthusiasm for work after carrying out the Inemuri program. However, several inhibiting factors still often arise that need attention from management so that the implementation of the Inemuri program is more optimal, including: 1) The inflexibility of the implementation time for the Inemuri program which is only limited to break time sessions; 2) The workload of employees, especially in the Sales Division, is often still high during break times, thus eliminating their 'right' to the Inemuri program, 3) The duration of implementing the Inemuri Program is too short, 4) Support from superiors is considered to be uneven, often making employees after The Inemuri program is still faced with a high workload, 5) Employees' stress management skills are not yet adequate, so they are quite susceptible to work stress, even though they have undergone the Inemuri program.   Keywords: Job Stress, Inemuri Program, Performance Management, Phenomenological Study.